Investigation about roles of the inferencial strategies in reading comprehension at high school education - Inga Arias, Miguel Gerardo (2014)
First, our investigation tries to determinate the role to perform the cognitive abilities, in particular about grammatical competence, the operative memory and inferences about the understanding reading of high school students, mainly fourth grade. In second place, investigate which of these habilities is preponderant to the efficient reading. For that, elaborated reactive to measure each one of this cognitive abilities, that results can make necessaries correlations that reach us several important conclusions to replanted pedagogic work at classrooms and orientated to metacognitive strategies more relevant. These major objectives demand to clarify these concepts to establish the most pertinent proposes to corresponding contrast. For that, we can support in theoretical framework what benefice to an extended range of linguistic, piscolinguistics and educative investigations. Then, we worked an epitome of those investigations. On that line, we have like a significant antecedent the behavior to these variables in college students who passed to general studies two years ago. This theoretical framework expressed a group of speculations with cohesion and coherence would be useful to establish the feasible hypothesis (or even a theory) in order to solve the problem or investigation problems. This scientific investigation started of a very explicit and exhaustive theoretical framework to stand sure about the epistemological interpretation to this particular work for the urgent problem of reading comprehension in our country.